Facilitators and barriers to patient-centred goal-setting in rehabilitation: A scoping review. (December 2022) - Crawford, L.; Maxwell, J.; Colquhoun, H.; Kingsnorth, S.; Fehlings, D.; Zarshenas, S.; McFarland, S.; Fayed, Nora
Objective: Identify, map, and synthesize existing reviews, to extract and analyse the most prominent barriers and facilitators to applying patient-centred goal-setting practice in rehabilitation using the Capability, Opportunity Motivation Behaviour (COM-B) model. Design: Scoping review. Data source: A primary search was conducted in MEDLINE, CINAHL, EMBASE, PsychInfo, and Cochrane. Citation chaining was employed. Review methods: All types of review (systematic, scoping, and narrative) studies published up to June 14, 2022 that included physical and neurological rehabilitation, patient-centeredness, and goal-setting were reviewed. Studies were scrutinized for relevance, quality was not assessed. The most prominent barriers and facilitators were synthesized using thematic content analysis and mapped onto the COM-B model. Results: Twenty-six review studies covering a range of conditions and settings, acute to community were included. Barrier and facilitators were identified at patient, provider, and organizational level. Barrier themes include provider's existing beliefs about goal-setting, lack of skills, and integration into clinical routines. Patient barriers related to capacity and opportunity to participate. Organizational barriers include lack of clinical guidelines, patient preparation, insufficient provider time, and high productivity expectations. Facilitators included goal-setting guidelines, training and education of providers and patients, revised clinical routines, performance monitoring, adequate time, and resources. Conclusion: Healthcare providers should be the primary target of intervention. A provider's motivation to change current practice is the most prominent barrier, followed closely by capacity and opportunity. Patients require information, training, and structured engagement opportunities. Organizations play a key role in creating the optimal environmental conditions to enable patient-centred goal-setting.